SYISTEMATIC LITERATUR RIVIEW: ANALISIS MANFAAT DIGITAL MOBILE JKN DALAM PEMBIAYAAN KESEHATAN - Dia Sari; Dwi Hirdanti, Nadia Syaibah Nasution, Fitriani Pramita Gurning (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2024)
The JKN Mobile App makes it easier for participants to use health services in a more efficient and effective way, reducing time and costs required. The app makes it easy for participants to see the fee payment, provides easy access to the services of FKTP (First Level Health Facility) and FKTL (Advanced Level Referral Facility), and allows the public to submit suggestions or complaints. Trouble in service. The purpose of this investigation is to find out the mobile benefits of JKN in health financing. In this writing, the Literature Review approach is implemented as a method. Literature review is a technique of collecting references that have been previously investigated, including theories and findings related to a phenomenon. These references are then analyzed after reading to serve as a foundation in writing. Data sources are obtained through journals or articles from various platforms such as Google Scholar, Scientists, Academia.edu, and Directory of Open Access Journals (DOAJ). The purpose of this literature review is to understand and compare previous research in the same field. In this writing, the author also conducted a study on the analysis of the use of JKN mobile in health financing. From the analysis carried out using the literature method of the mobile application JKN helped in the financing of health by making it easier for JKN participants in paying fees or accessing JKN like BPJS. With the presence of the JKN Mobile App, participants can now use the services more effectively and efficiently. In addition, there has been a decrease in the number of visits to BPJS Health offices, allowing more service focus on participants with special needs that cannot be dealt with through JKN mobile application.